(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The COVID-19 pandemic has precipitated unprecedented changes across various sectors, with education being one of the most significantly impacted. As higher education institutions swiftly transitioned from traditional in-person teaching methods to online platforms, the need to assess and understand this digital transformation has become critical. This research paper explores the adoption of online learning tools by higher education institutions in Haryana during the pandemic, employing a qualitative research methodology to gain deeper insights into the experiences, challenges, and outcomes associated with this shift.